Wortmannine H, a phenylpentenol isolated from an endophytic fungus, Talaromyces wortmannii LGT-4. Issue 19 (2nd October 2021) - Li, Xiao-Fei; Yang, Zhong-Duo; Yang, Xing; Yang, Li-Jun; Yao, Xiao-Jun; Shu, Zong-Mei
Abstract: A new phenylpentenol, wortmannine H (1 ) was isolated from Talaromyces wortmannii LGT-4, an endophytic fungus of Tripterygium wilfordii . The structure of 1 was elucidated by IR, MS, 1D and 2D NMR spectra and comparison of the experimental and calculated optical rotatory dispersion (ORD). Monoamine oxidase (MAO), acetylcholinesterase (AChE) and phosphoinositide 3-kinase (PI3Kα) inhibitory activities of 1 was also tested. The compound did not show good biological activity. Graphical Abstract: UF0001